1-week tour begins for G-G
tag=1 data=1-week tour begins for G-G tag=3 data=NT News tag=8 data=MONARCHY tag=9 data=GOVENOR-GENERAL%YEAR OF THE OUTBACK%MELVILE ISLANDTHURST ISLAND tag=32 data=HOLLINGWORTH, ANN%HOLLINGWORTH, PETER%BURKE, DENIS%MARTIN, CLARE tag=34 data=PRSS tag=61 data=09 tag=62 data=Jul tag=63 data= 2002